2012
DOI: 10.1098/rstb.2011.0186
|View full text |Cite
|
Sign up to set email alerts
|

Understanding chilling responses in Arabidopsis seeds and their contribution to life history

Abstract: Winter chilling is of central importance in the phenology of temperate annual and perennial plants. Chilling accelerates flowering through the process of vernalization and breaks both bud and seed dormancy, permitting the onset of growth in the spring. The quantitative effects of chilling in floral promotion in winter annual Arabidopsis accessions are well-documented, but very little is known about the basic physiology underlying summer annual responses to winter chilling, which acts on seeds within the soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 30 publications
8
86
5
1
Order By: Relevance
“…Low temperature also increases seed dormancy in wheat and this correlates with an increase in Ta-MFT gene expression (29). Once primary dormancy is released, secondary dormancy can be induced depending on environmental conditions (46). A recent study has demonstrated that secondary dormancy of Arabidopsis Cvi ecotype seeds correlated with low seasonal soil temperatures and high MFT expression (47).…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature also increases seed dormancy in wheat and this correlates with an increase in Ta-MFT gene expression (29). Once primary dormancy is released, secondary dormancy can be induced depending on environmental conditions (46). A recent study has demonstrated that secondary dormancy of Arabidopsis Cvi ecotype seeds correlated with low seasonal soil temperatures and high MFT expression (47).…”
Section: Resultsmentioning
confidence: 99%
“…Bayesian techniques show some promise in uncertainty analysis and for model calibration, and new methods are available for quantifying and attributing uncertainty in model outputs. Model data fusion offers new approaches to better combine models with diverse and complex datasets [55], while optimal fingerprinting using spatially and temporally explicit data will allow us to use models to attribute observed global changes to different drivers [51], which is of the utmost importance if we are to manage our planet to mitigate adverse impacts and to maximize benefits. As we increasingly employ systems approaches, and conduct research in multi-disciplinary teams, the transfer of skills, techniques and ideas across disciplines offers exciting opportunities for predictive ecology.…”
Section: Transferable Methods For Systems Ecology and Concluding Remarksmentioning
confidence: 99%
“…A common, simple model was applied that assigns one CU for each degree below T max , a temperature below which an organism perceives chilling (e.g. Luedeling et al 2009;Penfield and Springthorpe 2012). Daily chilling-units were thus calculated for the average daily temperature (T i ) that cysts experienced during cold storage using the following formula:…”
Section: Chilling-unit Calculationmentioning
confidence: 99%
“…A common model assigns one CU for each degree below T max , a temperature below which an organism perceives chilling (Luedeling et al 2009;Penfield and Springthorpe 2012). For A.…”
Section: Chilling-alleviated Dormancy Transitionmentioning
confidence: 99%